The KM3NeT data acquisition system - Status and evolution - Chiarusi Tommaso; Giorgio Emidio; Zito Daniele (EPJ Web of Conferences, 2023)
In this contribution, we present the data acquisition system system of the KM3NeT neutrino telescopes, ARCA and ORCA, already operating while under construction at the bottom of the Mediterranean Sea. The DAQ system implements a modular and scalable hardware-triggerless streaming readout of the optical modules in the telescopes. Handling a raw incoming throughput up to hundreds of Gbps, it is integrated with the online alert system of the KM3NeT Multimessenger program. The system will evolve according to a new design, currently under validation, which will grant the extension of the telescope to the aimed cubic kilometer scale.